Palladium supported on triazolyl-functionalized hypercrosslinked polymers as a recyclable catalyst for Suzuki–Miyaura coupling reactions. Issue 29 (1st May 2020) - Liu, Cijie; Zheng, Lijuan; Xiang, Dexuan; Liu, Shasha; Xu, Wei; Luo, Qionglin; Shu, You; Ouyang, Yuejun; Lin, Hongwei
Abstract : A novel hypercrosslinked polymer-palladium catalyst was prepared via external cross-linking reactions and applied in Suzuki–Miyaura reactions as a recyclable catalyst, resulting in TON numbers up to 1.66 × 10 4 and yields reaching 99%. Abstract : A novel hypercrosslinked polymers-palladium (HCPs-Pd) catalyst was successfully prepared via the external cross-linking reactions of substituted 1, 2, 3-triazoles with benzene and formaldehyde dimethyl acetal. The preparation of HCPs-Pd has the advantages of low cost, mild conditions, simple procedure, easy separation and high yield. The catalyst structure and composition were characterized by N2 sorption, TGA, FT-IR, SEM, EDX, TEM, XPS and ICP-AES. The HCPs were found to possess high specific surface area, large micropore volume, chemical and thermal stability, low skeletal bone density and good dispersion for palladium chloride. The catalytic performance of HCPs-Pd was evaluated in Suzuki–Miyaura coupling reactions. The results show that HCPs-Pd is a highly active catalyst for the Suzuki–Miyaura coupling reaction in H2 O/EtOH solvent with TON numbers up to 1.66 × 10 4 . The yield of biaryls reached 99%. In this reaction, the catalyst was easily recovered and reused six times without a significant decrease in activity.